Belief in Communism and Theory of Mind - Chen, Outong; Guan, Fang; Du, Yu; Su, Yijun; Yang, Hui; Chen, Jun (Frontiers in Psychology, 2021)
Belief in communism refers to the unquestionable trust and belief in the truthfulness of communism. Although former studies have discussed the political proposition and social value of communism, the cognitive neural basis of belief in communism remains largely unknown. In the present study, we determined the neural correlates of belief in communism using regional homogeneity (ReHo) and resting state functional connectivity (rsFC) as an index in resting-state fMRI (rs-fMRI), as measured by the Belief in Communism Scale (BCS). Results showed that belief in communism is associated with ReHo in the left thalamus and lower ReHo in the left medial frontal gyrus (MFG). Furthermore, results of the rsFC analysis revealed that the strength of functional connectivity between the left thalamus and the bilateral postcentral gyrus (PTCG) was negatively associated with belief in communism. Hence, this study provides the first evidence that spontaneous brain activity in multiple regions, which is related to the Theory-of-Mind (ToM), self-construal, and social cognition abilities, contributes to belief in communism.